Peranan Pengawasan dalam Meningkatkan Produktivitas Kerja Karyawan Divisi Marketing pada Koperasi UGT Sidogiri Kelurahan Bugih Pamekasan - Yanti Susanti; Fadllan Fadllan (Institut Agama Islam Negeri Madura, 2016)
Supervision is an examination to ensure that what is done in accordance with company goals, evaluating the implementation of the work, as well as improving what is being done to ensure the achievement of optimal results. Therefore, any financial institutions need to be done Supervision so that the achievement of set targets will be easily achieved, and preventing the occurrence of aberrations on what had been planned in advance. Issues to be discussed in this research first, how the implementation of the Supervision which is conducted at Cooperation UGT Sidogiri of the Village Bugih Pamekasan, and secondly, how the role of supervision in Increasing Employee Productivity Marketing Division at Cooperation UGT Sidogiri of Village Bugih Pamekasan. This type of research used is descriptive qualitative, which depicts or describes a case according to what is in the field. Sources of data are interviews, observation and documentation. Based on the research results, it can be concluded that: 1) Implementation of Supervision at Cooperation UGT Sidogiri of Village Bugih Pamekasan are: a) Supervision is done by the Branch Head of Cooperation UGT Sidogiri of Village Bugih Pamekasan, b) Supervision applied is Supervision directly and indirectly, periodic monitoring and supervision performed before activity, during the event, and after the activity. 2). The Role of Supervision in Increasing Employee Productivity Marketing Division at cooperation UGT Sidogiri of village bugih pamekasan is : a) to prevent the occurrence of various aberrations or errors, so it can be known earlier of various forms of aberration and errors.b) To guarantee or striving the implementation of activities to suit plans have been made before in order to achieve the goal. c) To correct errors or aberrations occurring.